Beyond the immediate: exploring the long-term effects of COVID-19 on urban retail in Seoul, South Korea - Kyeong Hee Seo (Journal of Asian Architecture and Building Engineering)
This study examines the impact of COVID-19 on Seoul’s urban retail areas using a fixed-effect panel model over 49 months. Findings reveal a 1.6% year-over-year revenue decline as case density increases, exacerbated by government quarantine measures. We analyze how distancing policies affected retail revenues based on area type, pre-pandemic revenue, franchised store proportion, proximity to public transportation, and Points of Interest. Results indicate the necessity for tailored infectious disease prevention strategies that consider diverse retail environments and highlight the significant influence of population demographics on revenue dynamics. The study emphasizes the importance of a balanced mix of workers and residents in office-dense neighborhoods to enhance resilience during health crises. Additionally, it advocates for targeted support for small businesses and continued investment in public services to maintain neighborhood vibrancy. These policy recommendations align with the need for place-based strategies to mitigate the socio-economic impacts of pandemics, as emphasized by international organizations. By adopting nuanced, context-specific approaches, cities can better prepare for and respond to future health crises while fostering sustainable urban systems and economic resilience.